2014
DOI: 10.1007/s00300-014-1532-8
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interannual variation in the diet of the Magellanic penguin (Spheniscus magellanicus) at Martillo Island, Beagle Channel

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag Berlin Heidelberg. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 48 publications
3
40
0
2
Order By: Relevance
“…Additionally, many studies often lack independent, quantitative estimates of prey abundance (e.g., Scioscia et al, 2014;Webb and Harvey, 2014). Some studies, however, have shown similar narrowing of dietary niches under changing availability of key prey species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many studies often lack independent, quantitative estimates of prey abundance (e.g., Scioscia et al, 2014;Webb and Harvey, 2014). Some studies, however, have shown similar narrowing of dietary niches under changing availability of key prey species.…”
Section: Discussionmentioning
confidence: 99%
“…Shoals of Fuegian Sprat Sprattus fueguensis , an important prey for southern Magellanic Penguin colonies (Radl & Culik , Scioscia et al . ), exhibit a diel cycle, in which they disperse in superficial layers during night‐time (5–10 m) and descend (maximum 70 m), whereas during the day they form compact shoals (Sánchez et al . , Casarsa ).…”
Section: Discussionmentioning
confidence: 99%
“…, Scioscia et al . ) by Magellanic Penguins along their distribution, which reflects the availability of prey resources across their distribution range.…”
mentioning
confidence: 99%
“…A similar approach was taken in estimating the trophic level of Magellanic penguins breeding at Isla Martillo. At this location Magellanic penguins fed mainly on fuegian sprat (TL = 4.1, Sprattus fuegensis), representing 55% of the biomass consumed by birds (Scioscia et al, 2014). The next most important prey item was squat lobster 27 % (TL = 2.7, Munida gregaria) followed by Patagonian squid 14% (TL = 3.8, Loligo gahi) and 4% other prey (Scioscia et al, 2014).…”
Section: Trophic Level Calculationsmentioning
confidence: 98%
“…At this location Magellanic penguins fed mainly on fuegian sprat (TL = 4.1, Sprattus fuegensis), representing 55% of the biomass consumed by birds (Scioscia et al, 2014). The next most important prey item was squat lobster 27 % (TL = 2.7, Munida gregaria) followed by Patagonian squid 14% (TL = 3.8, Loligo gahi) and 4% other prey (Scioscia et al, 2014). The proportion of each prey type in the diet along with the trophic level of common prey species were incorporated into formula (3), above, to estimate trophic level of King and Magellanic penguins (IM).…”
Section: Trophic Level Calculationsmentioning
confidence: 99%